Sophistry is detected and dismantled, not believed (Journal of Parents and Teachers, 2023)
Every day we read newspapers in search of reliable information to find out what is going on. Sometimes certain publications are sophistry, so it is important to know some typical styles in order to avoid them.
Keywords: sophistry; information; publication